The prognostic and clinicopathological significance of PD-L1 expression in patients with diffuse large B-cell lymphoma: a meta-analysis - Qiu, Liping; Zheng, Hanlu; Zhao, Xiaoying (BMC cancer, 2019)
Programmed cell death receptor 1 ligand 1 (PD-L1) expression in various tumors, including hematologic malignancies, has recently become a research topic of great interest. We performed a meta-analysis to evaluate the prognostic and clinicopathological value of PD-L1 expressed in tumor cells of patients with diffuse large B-cell lymphoma (DLBCL). Relevant studies were identified from PubMed, EMBASE, Web of Science and the Cochrane Library. The hazard ratio (HR) and 95% confidence interval (95% CI) were used for analyzing survival outcomes, and the odds ratio (OR) was used for analyzing clinicopathological parameters. Pooled results showed that tumor cell PD-L1 expression is associated with poor overall survival (OS) (HR = 2.128, 95% CI: 1.341-3.378, P = 0.001), the non-germinal center B-cell-like subtype (OR = 2.891, 95% CI: 2.087-4.003, P < 0.000), high international prognostic index score (3-5) (OR = 1.552, 95% CI: 1.111-2.169, P = 0.010), B symptoms (OR = 1.495, 95% Cl: 1.109-2.015, P = 0.008), positive MUM1 expression (OR = 3.365, 95% Cl: 1.578-7.175, P = 0.002) and negative BCL6 expression (OR = 0.414, 95% Cl: 0.217-0.792, P = 0.008). Sensitivity analysis showed that there was no publication bias among these studies. Our meta-analysis supported the idea that tumor cell PD-L1 expression may represent a promising biomarker for predicting poor prognosis and is associated with adverse clinicopathologic features in DLBCL patients.